Skills for effective learning in school : supporting emotional health and wellbeing in school - Waterhouse, Alison, 1963- (Routledge, 2019)
"Skills for Effective Learning in School offers research-driven, practical strategies, resources and lesson plans to support educators and health professionals. This is a resource book for practitioners looking to have a positive impact on the mental health and wellbeing of the children and young people in their care; both now and in the future. Offering research-driven, practical strategies and lesson plans, Skills for Effective Learning in School is an essential resource book for educators and health professionals looking to have a positive impact on the mental health and wellbeing of the children in their care; both now and in the future"--